Endoscopic Management of Foreign Body Impaction in the Upper Gastrointestinal Tract in a Tertiary Care Centre of Nepal - Shrestha, A.; Gurung, R.B.; Sharma, P.; Shrestha, R.; Shrestha, P. (Kathmandu University Medical Journal, 2020)
Background Ingested foreign body impaction on upper gastrointestinal tract is common incidence among children, older age group, mentally challenged individuals, and people the influence of alcohol. In most cases, the foreign bodies pass spontaneously and uneventfully but when this does not occur; endoscopic management to ensure removal under direct visualization is required. Relief upon removal of foreign body and prevention of complications is essential.Objective To assess the endoscopic management and outcome of foreign body impacted in the upper gastrointestinal tract.Method This is a hospital based observational retrospective cross sectional study involving 165 patients at Endoscopy Department of Dhulikhel Hospital in Nepal between November 2015 and October 2019. The data regarding the demographic profile, clinical characteristics and endoscopic findings were retrieved and analyzed to determine endoscopic interventions performed, complications and outcomes.Result One hundred and sixty five patients presenting with history of ingestion of foreign body were included in the study. The mean age of the patients was 46.8 ± 19.1 years with male predominance (60%). The most common site of foreign body impaction was oesophagus (70%). The most common foreign body encountered was bone (62.2%) among which chicken bones (91.1%) were most frequent. For the retrieval of sharp-pointed foreign bodies, rat forceps and graspers (45.7%) were most commonly used. Total 14 cases required rigid oesophagoscopy as the foreign body could not be retrieved by flexible endoscopy.Conclusion Foreign body ingestion and its impaction in the upper gastrointestinal tract has been found to be common in endoscopic practise. Early detection and timely removal of foreign bodies is of utmost importance to avoid discomfort to the patient as well as to ensure successful removal without complications.